Effectiveness study on multimedia mobile application for children: Mfolktales - Ibrahim, N. (Asian Research Publishing Network, 2016)
Mobile application has been used widely among children as a supplement for learning purposes. These handheld technologies such as smart phone and tablet have been chosen as they are easy to carry anywhere and anytime and easy to get as they are become cheaper nowadays. Following from that, a mobile application called MFolktales have been designed and developed for children to promote Malay folktales to the new generation as Malay folktales became extinct and almost forgotten. This paper discusses the effectiveness testing for MFolktales application to measure effectiveness level in studentsâ comprehension performance after using the MFolktales mobile application. In the other hand, the study also conducted to evaluate the hypotheses to summarize the relationship between the samples that have been used in the testing. The testing was conducted among 90 students aged 5 and 6 years old which then divided into three groups which are control group (CG), experimental group 1 (EG1) and experimental group 2 (EG2). CG and EG1 are control groups while EG2 is experimental group. Result from the post-test show that, there is a significant difference between the post-test means scores of the students in CG, EG1 and EG2. Results also show that, there is a significant difference between the mean scores for the students in CG, EG1 and EG2. Thus, MFolktales application can be considered as effective. Â© 2005 - 2016 JATIT & LLS. All rights reserved.